The Thermal Performance of Vernacular Houses as An Identity of Kurdish Traditional Architecture - Raof, Binaee Yaseen; Dhiaadin Bahaadin, Sara; Qadir Rasul, Hoshyar (Kurdistan Journal of Applied Research, 2020)
Nature in general and especially climate, play a decisive role in defining the architecture of a place or people over time. Therefore, it is more convenient to look at architecture as a mirror reflects people's adaptation and behavior to the environment over time. Because of mainstream design with low-tech conditions, the climate is the predominant power that characterizes the building types. In this manner, as long as the climate differs from one place to another, the vernacular architecture is going to be differs as well, due to the environmental conditions. Traditional houses were adopted to meet the basic psychological and physiological needs of man through the most rational elements, such as building floor plans (spatial organization), materials, shapes, details and floor effects in various ranges. As a result, these architectural features marked the identity features of local architecture in the city. For this reason, the paper focuses on testing the thermal performance of some types of vernacular houses commonly used in the city of Sulaimani, especially in the traditional zone of the city. To achieve the research objectives, the study followed experimental analytical methodology, using outputs of the most appropriate software (Design Builder) to test the performance of three common types of local traditional houses (single and double floors). It appears that the type L with single floor is the most efficient, but the U shape with single floor recorded the highest number of days throughout the year when energy was needed.